A group housing society ontology in Swoop 2.3 Beta 4 and Protege 3.4.4. (1st January 2014) - Malik, Sanjay Kumar; Rizvi, S.A.M.
Ontology creation using various editors like Protégé and SWOOP plays a significant role in Semantic Web. In this paper, we illustrate the creation of a housing society ontology viz, 'Jawaharlal CGHS ontology' using Swoop and Protégé, the most commonly used ontology editors. We are using Swoop 2.3 Beta 4 editor where super class and sub class hierarchy and instances have been presented with the query retrieval process using 'Fly the MotherShip' option in advanced tab and show the 'general concept inclusion axiom', 'class expression table' for relations in classes and subclasses. Then, the same ontology is created using Protégé 3.4.4 and finally illustrates using the OWL code to obtain ontology class hierarchy (subject/object relationship) in Protege by executing a SPARQL query.